(untitled) (Fiep Bulletin - online, 2015)
The objective of this article was to analyze one of the dilemmas faced by some professional soccer players in the last decade: the right to reinstatement to the amateur status, as a mechanism to continue reaping the financial benefits that the amateur status can provide. Quitting professionalism is initially sustained by three perspectives: a) look for a stable salary in another profession, through his sport competence in representing the employer company in amateur soccer leagues; b) right to informal wages in amateur soccer clubs; and, c) request free pass for a new restart in another professional club. In this way, we will attempt to analyze the amateur re-significance in the organizational structure of the Brazilian soccer. Our sources are CBF official documents, newspaper articles and an interview with a professional former-athlete that applied to CBF for reinstatement to amateur status. The analysis demonstrates that: a) the soccer market is not limited the main leagues and other forms of carrying out the profession that the legal soccer structure insists on classifying it as amateur in spite of the social dynamics; b) the reinstatement mechanism demonstrates anachronism and adaptation before/in front the labor relationships enlarged by the business soccer market.